Parasymphysial and intracapsular condylar fracture in a pediatric patient managed with resorbable plates: a case report - Díaz Príncipe, Fernando Ernesto (2019)
The mandibular fracture is one of the most common types in pediatric maxillofacial trauma. The main objective of fracture management is the restoration of bone shape and function. Incomplete fractures are more common due to bone elasticity; so, usually the treatment of fractures in children is conservative. Due to the progress on materials bone reparation and technological improvement, currently the proportion of children treated with open reduction and internal fixation (RAFI) has increased. The use of miniplates and miniscrews are the gold standard treatment for craniomaxillofacial semirigid fixation. One alternative are the resorbable materials, which do not require the removal and are gradually degrade. This is a considerable advantage for the management of mandibular fractures in children. We present the case of a 6-year-old patient who suffered a parasympathetic mandibular and condylar fracture. The clinical examination showed limited oral opening and moderate pain on palpation. The radiological evaluation evidenced parasymphyseal and intracapsular fracture traces on the left condyle. These fractures were managed with resorbable plates and conservative treatment, respectively. The result was optimal.